Tardive Dyskinesia After Aripiprazole Treatment That Improved With Tetrabenazine, Clozapine, and Botulinum Toxin - Aguilar, Lourdes; Lorenzo, Carolina; Fernández-Ovejero, Raquel; Roncero, Carlos; Montejo, Angel L. (Frontiers in Pharmacology, 2019)
We report on a patient with tardive dyskinesia (TDK) treated with aripiprazole, a third-generation antipsychotic with partial D2 agonist-antagonist activity at both the dopamine and serotonin receptors. The patient’s condition improved with administration of a combination of tetrabenazine, botulinum toxin, and clozapine, which has previously not been used. We suggest that this treatment combination may have potential benefits for patients with TDK. After aripiprazole discontinuation, the patient was treated with clozapine (150 mg/day) and biperiden (8_mg/day). Due to a lack of improvement, we administered 300 units (intramuscularly; IM) of botulinum toxin into the paravertebral muscles every three months and 1,000 units IM every four months in addition to tetrabenazine (75 mg/day) and biperiden (8 mg/day). The patient stopped this treatment, at which point TDK reappeared. After starting a treatment regimen of clozapine (100 mg/day), tetrabenazine (75 mg/day), and botulinum toxin (300 units IM), the patient’s symptoms remitted.